Studying Air Pollutants Origin and Associated Meteorological Parameters over Seoul from 2000 to 2009 - Sunmin Park; Hesham El-Askary; Ismail Sabbah; Hanbin Kwak; Anup K. Prasad; Woo-Kyun Lee; Menas Kafatos (Advances in Meteorology)
We investigate the temporal characteristics of major air pollutants collected from 44 air quality stations over the city of Seoul, Korea, namely, nitrogen dioxide, carbon monoxide, particular matter at 10 microns, and sulfur dioxide (SO2) between 2000 and 2009. The corresponding satellite datasets, namely, aerosol optical depth (AODsat), Ångström exponent, and fine mode fraction, collected from moderate resolution imaging spectroradiometer (MODIS) as well as the Aeronet ground aerosol optical depth (AODaeronet), have been analyzed. Pollutants’ seasonal effect has been inferred from the precipitation and temperature. The four pollutants under study show varying temporal characteristics with different annual mean concentration patterns. The monthly mean of mentioned pollutants all show similar low concentrations during the summer season and high concentrations during the winter season. We found that pollution is strongly linked to temperature and precipitation variability, especially during the fall season. Satellite data analysis provides information on the pollutants origin whether of natural or anthropogenic type. Our results indicate that the anthropogenic aerosol is dominant in the summer season even though the concentration was lower than the other seasons. AODaeronet and Ångström exponent indicated high positive and negative correlation coefficients with PM10, 0.60, and −0.45, respectively. Both small and large sizes of aerosols existed in 2007; however coarse size of aerosols was the primary component in 2002.